2004
DOI: 10.1111/j.1365-246x.2004.02200.x
|View full text |Cite
|
Sign up to set email alerts
|

3-D finite-element modelling of deformation and stress associated with faulting: effect of inhomogeneous crustal structures

Abstract: S U M M A R YModelling of deformation and stress caused by earthquake faulting (or fault motion) based on a homogeneous elastic half-space model does not include crustal rigidity layering and lateral variations. Geological data and seismic surveys indicate that the crust is elastically inhomogeneous, and that rigidity layering and heterogeneities are likely to affect the magnitude and pattern of deformation and stress. We use the finite-element method (FEM) to investigate deformation and stress generated by st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 52 publications
3
46
0
Order By: Relevance
“…To check the reliability of the results, we calculate fields of displacement and stress produced by the same dislocation on the same fault in the half-space elastic medium by using Okada's method [11] . Following some others [12,39] , we present comparison between distribution of displacement and maximum shear stress on the surface in Figure 5. It shows that the results derived from finite element method and classic analysis method are consistent.…”
Section: Comparison Of Results Derived From Finite Element Model and mentioning
confidence: 98%
See 1 more Smart Citation
“…To check the reliability of the results, we calculate fields of displacement and stress produced by the same dislocation on the same fault in the half-space elastic medium by using Okada's method [11] . Following some others [12,39] , we present comparison between distribution of displacement and maximum shear stress on the surface in Figure 5. It shows that the results derived from finite element method and classic analysis method are consistent.…”
Section: Comparison Of Results Derived From Finite Element Model and mentioning
confidence: 98%
“…Some researchers [9,10] studied the triggering mechanism between major earthquakes along the Xianhuihe fault zone by using the homogeneous elastic dislocation model [11] . However, if the media is assumed to be half-spatially homogeneous in the dislocation model, the difference is big between the results derived from homogeneous dislocation model and elastic layered model [12] . In addition, the influence degree on the subsequence earthquakes along the fault zone by the interaction between major earthquakes was ignored in previous study.…”
Section: Introductionmentioning
confidence: 97%
“…Rather than using an elastic half-space or layered-earth model, realistic geologic structures and heterogeneous physical properties can be used to calculate seafloor displacement, most often by finite element methods (Geist and Yoshioka 1996;Masterlark 2003;Zhao et al 2004). Static elastic deformation models developed for the Nankai subduction zone were adapted to calculate tsunami Encyclopedia of Earthquake Engineering DOI 10.1007/978-3-642-36197-5_296-1 # Springer-Verlag Berlin Heidelberg (outside the USA) 2014 generation along the Cascadia subduction zone (Geist and Yoshioka 1996).…”
Section: Dislocation Models Of Tsunami Generationmentioning
confidence: 99%
“…However, seismic surveys and geological investigations have indicated that the subsurface include various scales of heterogeneities which might have the influence on the estimation of the stress fields in the subsurface generated by earthquakes. Zhao et al (2004) investigated deformation and stress generated by strike-slip, tensile and thrust faulting, considering the rigidity layering in the crust. They showed that the surface deformation and stress changes are distorted by the ignorance of crustal structural information.…”
Section: Introductionmentioning
confidence: 99%